Learning Circle Using Gobak Sodor Game Context In Eighth Grade - Harisman Nizar; Dyah Rahmawati (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2024)
This research aims to produce a learning trajectory that can help students understand the concept of circles using the Indonesian Realistic Mathematics Education (PMRI) approach. This research takes the context of the traditional game